Evaluation of radiographic knee OA progression after arthroscopic meniscectomy compared with IACI for degenerative meniscus tear - Hairui Zhang; Zhiyao Zhao; Fangzheng Zhou; Xiaoning Liu (Scientific Reports)
Abstract The intra-articular corticosteroid injection (IACI) and arthroscopic partial meniscectomy (APM) are crucial treatment options for meniscus tears and are widely used in clinical practice. To determine whether there are differences in the progression of osteoarthritis (OA) after APM and IACI treatments for degenerative meniscal tears, and to identify the influencing factors. We finally collected the minimum joint space width (JSW), WOMAC score, and KOOS score of 189 patients after 4 years of follow-up. The mixed effects model and general estimating equation were used to analyze the differences in the progression of knee osteoarthritis and the factors affecting the progression of knee osteoarthritis in patients with degenerative meniscus tears who received different treatments. Over a 48-month follow-up period, all three groups showed a decreasing trend in knee JSW, with the IACI group having the fastest JSW decline rate at -0.020 mm/month (95% CI: -0.027 to -0.013, p < 0.01). There was no statistically significant difference in the JSW decline rate among the three groups. The WOMAC total scores for both the IACI and APM groups showed an improving trend, at -0.123/month (95% CI: -0.211 to -0.036, p < 0.01) and − 0.115/month (95% CI: -0.201 to -0.028, p < 0.01) respectively, with no statistical difference between the two groups. BMI was also a significant factor affecting postoperative JSW (regression coefficients: -0.012, 95% CI: -0.022 to 0.001, p = 0.03) and WOMAC total scores (regression coefficients: 0.189, 95% CI: 0.008 to 0.370, p = 0.04). Compared to single IACI, multiple IACI treatments resulted in faster JSW decline (B: 0.430, 95% CI: 1.012 to 2.336, p = 0.04). Patients with degenerative meniscal tears who undergo either IACI or APM treatment exhibit more pronounced progression of knee osteoarthritis compared to those in the non-treatment group. This form of deterioration is mainly driven by BMI.